2013
DOI: 10.1111/eos.12107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of enamel demineralization by buffering effect of S‐PRG filler‐containing dental sealant

Abstract: The buffering capacity and inhibitory effects on enamel demineralization of two commercially available dental sealants were evaluated in this study. The effects of filler particles were also examined. Disks of enamel and cured sealant materials of BeautiSealant (silica or S-PRG filler) or Teethmate F-1 were incubated in lactic acid solutions (pH 4.0) for 1-6 d. The pH changes and amounts of ions released in the solutions were assessed, and enamel surfaces were observed using a scanning electron microscope. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 30 publications
8
85
2
1
Order By: Relevance
“…The results of our study confirmed the findings of previous studies showing that glass-ionomer material increased the pH of a lactic solution 13,42) . In agreement with previous studies, we determined that calcium aluminate cement and silica filler also increase the pH of an acid solution 43,44) . Higher pH tends to reduce demineralization and stimulate remineralization, resulting in a reduced prevalence of dental caries 13,42) .…”
Section: Discussionsupporting
confidence: 92%
“…The results of our study confirmed the findings of previous studies showing that glass-ionomer material increased the pH of a lactic solution 13,42) . In agreement with previous studies, we determined that calcium aluminate cement and silica filler also increase the pH of an acid solution 43,44) . Higher pH tends to reduce demineralization and stimulate remineralization, resulting in a reduced prevalence of dental caries 13,42) .…”
Section: Discussionsupporting
confidence: 92%
“…Strontium and fluoride also increase the acid resistance of teeth by converting hydroxyapatite to strontium apatite and fluorapatite (29). S-PRG fillers exert a modulation effect that neutralizes the pH of the surrounding environment after contact with acidic solutions (30). The present study was adequately randomized and patients who did not maintain an acceptable standard of oral hygiene were not excluded from the study.…”
Section: Secondary Caries Alpha No Clinical Diagnosis Of Caries Bravomentioning
confidence: 99%
“…A surface reaction-type pre-reacted glassionomer (S-PRG) filler forms a stable glass-ionomer phase by pre-reacting acid-reactive glass-containing fluoride with polycarboxylic acid in the presence of water [13][14][15] , and it can release Al, B, F, Na, Si, and Sr ions. Supplying Si and Na ions into the surrounding environment leads to a buffering effect 16,17) , further inhibiting demineralization. In addition, Si and F ions are known to improve the acid resistance of teeth by converting hydroxyapatite to strontiumapatite 18,19) and fluoroapatite, respectively [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%